The Impact of Angiotensin-Converting Enzyme Inhibitors on Immune-Related Adverse Events and Clinical Outcomes in Patients with Metastatic NSCLC - Noa Shani Shrem; Samer Abu-Rafe; Abed Agbarya; Ashraf Abu Jama; Asmah Miari; Ronen Brenner; Yulia Dudnik; Adan Khalaily; Alexander Yakobson; Samer Hussany; Raya Bdair; Keren Rouvinov; et al. (Biomedicines, 2026)
Background: The integration of immune checkpoint inhibitors (ICIs) has transformed metastatic non-small cell lung cancer (NSCLC) therapy. However, the immunomodulatory influence of concurrent medications, including angiotensin-converting enzyme inhibitors (ACEIs), remains poorly defined in real-world practice. Methods: This retrospective observational study included 452 patients with metastatic NSCLC treated with first-line ICI-based therapy (ICI monotherapy or chemo-immunotherapy) between 2017 and 2025. Patients were stratified according to chronic ACEI exposure, defined as administration for >2 years. Primary endpoints were overall survival (OS), progression-free survival (PFS), and immune-related adverse events (irAEs). Results: Among 452 patients, 71 (15.7%) were chronic ACEI users. ACEI use was associated with significantly longer median OS in univariable analysis (17.0 vs. 14.0 months; HR = 0.78, 95% CI: 0.61–0.99; p = 0.047) and a favorable trend toward improved PFS (14.0 vs. 11.0 months; HR = 0.81, 95% CI: 0.64–1.02; p = 0.066). ACEI users had higher rates of cutaneous rash (25.4% vs. 13.1%; p = 0.011) and transaminase elevation (29.6% vs. 8.9%; p < 0.001). Severe grade 3–5 irAEs remained uncommon and did not differ significantly between groups (p > 0.05). Conclusions: Chronic ACEI use was associated with longer OS in univariable analysis, but this association was not statistically significant after multivariable adjustment. ACEI use was also associated with increased low-grade cutaneous and hepatic toxicities without a significant increase in severe irAEs. Prospective studies are warranted to clarify the clinical significance of these associations.